REPORTING ON THE REASONS FOR THE ACQUISITION OF OWN SHARES - Pavlović, Vladan; Cvijanović, Janko; Milačić, Srećko (Economics of Agriculture, 2014)
Mere knowledge that the company has acquired own shares is not always of great importance. Information on the acquisition of own shares from dissenting shareholders or the squeeze-out of minority shareholders is not of great importance to the users of fnancial statements. In the frst case, it is far more signifcant to disclose the significant event that allowed dissenting shareholders to resign from the company. However, the purchase of own shares due to certain reasons, such as the purchase of own shares at a premium in order to influence the market value of shares, the repurchase focused on preventing greater harm to the company, which is especially true at a time of financial crisis, or the repurchase of own shares as a means of disbursing shareholders, is of great importance to the users of fnancial statements. Therefore, modern legislation in developed countries obliges companies to disclose a range of information regarding own shares, including the reasons for the acquisition. The above is also proscribed by the relevant EU directives and national legislation. The paper points out that the legal norms governing the obligation of reporting on own shares in Serbia are not harmonized and that most public companies in Serbia, despite the legal obligation, do not disclose the reasons for the acquisition of own shares.